Efficacy and safety of taxanes combined with chemotherapy drugs in advanced triple negative breast cancer: A meta-analysis of 26 randomized controlled trials - Huang, Qionglian; Mei, Zubing; Han, Xianghui (Frontiers in Oncology, 2022)
Background: Background: Researchers have demonstrated that the combined use of taxanes and chemotherapy drugs, especially paclitaxel-based treatment, appeared to clinically benefit on advanced triple negative breast cancer (TNBC). This meta-analysis aims to obtain the existent evidence on efficacy and safety for taxanes-based combination therapy to treat advanced TNBC. Methods: From 1991 to June 2022, 7 databases (PubMed, Web of Science, Cochrane Library, Embase VIP, Wanfang and CNKI databases) were comprehensively searched with no restricted language and region. The included Randomized controlled trials (RCTs) compared taxanes-based combination therapy versus taxanes or other chemotherapy drugs. Statistical analysis was conducted using random-effect model and the quality of RCTs was assessed using the tool of Cochrane Collaboration risk of bias. Results：Twenty-six RCTs with a total of 8236 advanced TNBC patients were included. Compared with taxanes monotherapy, taxanes-based combination therapy significantly prolonged progression-free survival (HR=0.79, 95%CI=0.74-0.83, I2=0.0%, P=0.000) and overall survival (HR=0.88, 95%CI=0.82-0.94, I2=9.3%, P=0.000), increased the risk of vomiting (RR=1.26, 95%CI=1.07-1.48) and diarrhea (RR=1.82, 95%CI=1.22-2.70, I2=90.3%, P=0.003). No statistical differences were observed in complete response rate (CRR), objective response rate (ORR), disease control rate (DCR) and progressive disease (PD) indexs (CRR: RR=1.38, 95%CI=0.96-1.99; ORR: RR=1.20, 95%CI=0.73-1.98; DCR: RR=1.09, 95%CI=1.00-1.19; PD: RR=0.70, 95%CI=0.47-1.04). Compared with other chemotherapy drugs, taxanes plus other chemotherapy drugs significantly reduced the incidence of vomiting (RR=0.60, 95%CI=0.44-0.84, I2=12.3%, P=0.002) and neutropenia (RR=0.58, 95%CI=0.35-0.96, I2=73.0%, P=0.036) during the treatment period. Notably, taxanes plus bevacizumab could evidently improve ORR index and decreased PD index in patients compared to bevacizumab plus other drugs (P<0.05). Conclusions: Taxanes-based combination therapy is evidently effective and well-tolerated in advanced TNBC, indicating that it might be a recommended option for treating advanced TNBC patients to some extent.